Harrison's gastroenterology and hepatology - Fauci, Anthony S., 1940-; Harrison, Tinsley Randolph, 1900-1978.; Langford, Carol A.; Longo, Dan L. (Dan Louis), 1949- (New York : McGraw-Hill Medical, 2013)
Featuring a collection of chapters on gastroenterology and hepatology from Harrison's Principles of Internal Medicine, Eighteenth Edition and the companion DVD, this concise clinical companion also includes updates and new developments, and board review questions. It is ideal for the classroom, wards, or exam/certification preparation. Features: full-color presentation; content derived from Harrison's, the world's leading and most trusted medical text; convenient, carry-anywhere presentation
Includes index
This book is aimed at bringing together the chapters of the current and 18th edition of Harrison's Principles of Internal Medicine related to gastroenterology and hepatology in a conveniently sized book for a focused study of this medical subspecialty
Includes bibliographical references and index
13
Keywords: Gastroenterology -- Textbooks; Gastrointestinal Diseases; Liver Diseases